Diseño de una estrategia metodológica para el desarrollo de la clase de educación física de 10mo año de la Unidad Educativa Galo Plaza Lasso del cantón Echeandía, Provincia Bolívar en el retorno presencial post covid-19 - Maridueña Campos, Mariuxi Ángela (2022)
The objective of this research is to design a methodological strategy for the development of the physical education class of the 10 th year of the “Galo Plaza Lasso” Educational Unit of The Echeandía canton Bolívar province in the face-to-face return post COVID 19. Theoretical and empirical methods were used. A qualitative and quantitative methodology, cross-sectional and descriptive in nature. Deductive-inductive, descriptive methods were the interview and the survey. Intentionally, 3 physical education teachers, 1 director of institution and 46 students were taken for interviews. The information obtained allowed us to understand the phenomenon studied and outline the methodological strategies focused mainly on excesses that develop coordination movement, while enhancing the game as a way to motivate student to forget about the problems left by the pandemic and to think in themselves